Expression of the feelings of the characters and impact on the spectators in Seneca ’s dramas - Dikmonienė, Jovita (Literatūra, 2008)
On the basis of the works by Taplin, Nussbaum, and Schiesar, the article explores the feelings of the protagonists of Seneca’s tragedies, Thyestes and Medea, which are the factors that develop the plot and the dynamics of the tragedies. The article also reviews the emotions these tragedies may set up in the spectators and readers. A comparison is draw between these tragedies and three philosophical dialogues of Seneca On Anger. The article investigates why and how the hatred and fury of the protagonists grows and develops. Anger is shown as pain by Seneca. Such words as ira and dolor are used as synonyms in the tragedies. The protagonists’ emotions of anger and rage cause the spectators’ fear.In Thyestes and Medea, very much like in his philosophical piece On Anger, Seneca discloses the feeling of anger of the main characters in three stages. In the first stage, the poet depicts involuntary anger of Medea with Jason who has broken the vows of love. In Thyestes, Atreus is angry with Thyestes who has insulted his glory. In stages one and three the characters talk to their spirit and the feeling of anger as if with an ostensible, imaginable interlocutor. In stage two, Seneca discloses extensive pride of the protagonists, the feeling of anger that is managed and controlled, their accusations to the offenders, and their wilful determination to revenge. In stage three, the poet depicts wild and uncontrollable anger and fury when Medea and Atreus kill children not because of any need, but because the passion of anger blinds the wisdom. The first and third stages of anger are shown by Seneca as uncontrollable and unconscious, whereas the second stage of anger –  a conscious when the protagonists can control their passions, yet they succumb to them.In the tragedies, like in the essay On Anger, Seneca focuses on the depiction of the consequences of anger and the damage that the failure to control anger in due time brings to a man and the people around him. The article concludes that tragedies, like diatribes, had similar therapeutic and didactic aim with respect to the readers and spectators. The poet said that the spectators, frightened and appalled with the passion of anger, would try to know themselves better, sustain from outrage, accusations, and revenge; they would understand that people’s relationships should be based on love and mercy rather than anger and violence.